KEMAMPUAN REPRESENTASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI PROGRAM LINEAR DI MAN2 PONTIANAK - Juniati, Nani Ika; Jamiah, Yulis; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research aim to describe the ability of students mathematical representation in accomplishing contextual problem of linear programming. This research used descriptive method. Subjects in this research were students of class XI MIA. Based on the analysis of research data obtained are: (1) the students ability of table representation of linear programming included in the high criteria with percentages 87,84% and the average score was 3,51; (2) the students ability of model mathematic of linear programming included in the medium criteria with percentages 68,24% and the average score was 2,73; and (3) the students ability of problem solvingrepresentation of linear programming included in the medium criteria with percentages 43,24% and the average score was 1,73. The ability of students mathematicals representation are in medium criteria with a percentages 66,44% and the average score was 2,66. Keyword:The Ability of Mathematical Representation, Contextual Problem, Linear Programming